Periodic fever, aphthous stomatitis, pharyngitis, and cervical adenitis syndrome (PFAPA) or recurrent urinary tract infections: a case report - Banafshe Dormanesh; Maryam Asli; Roya Daryanavard; Peyman Arasteh (BMC, 2022)
Abstract Background Fever is the most frequent reason for medical consultation in children, and makes up 15-25% of all consultations in primary care and emergency departments. In here we report a case of a 13 year-old girl who referred with an unusual presentation of fever and was misdiagnosed with recurrent urinary tract infection for 8 years. Case presentation This is a Clinical Reasoning Cycle case study. A 13 year-old girl was referred with a chief complaint of recurrent fevers from 8 years. During her first febrile episode, she had a 5-day high-grade fever associated with loss of appetite. Her physical examination at that time was unremarkable. Blood tests showed leukocytosis with a shift to the left and urine examination was in favor of pyuria. The urine culture was positive for bacterial growth. The episodes of fever were repeated every 45 days. Accordingly, the patient was diagnosed as a case of recurrent urinary tract infection. In the intervals between her febrile episodes, the patient was healthy and laboratory tests were normal. Ultrasonography, voiding cystourethrogram and dimercaptosuccinic acid scans were normal. During her last visit, the patient mentioned difficulty in swallowing and on examination cervical lymph nodes, exudative tonsillitis and painful aphthous stomatitis were detected. All antibiotics were stopped and corticosteroids were started. The patient's symptoms were relieved and the interval between her febrile episodes became longer. Conclusions Our study shows that a patient should never be marked, particularly when the symptom and signs aren't completely justifying a patient's condition.